2022 End Year Homecoming: News Analysis About Policy Dynamics - Siswanta; Mohammad Sawir; Muhammad Kasim; Nanda Saputra; Iskandar (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2023)
Online news grows up to be influential day by day, especially after the world facing a great disaster of COVID-19 Pandemic. When the Pandemic is over, 2022 is marked to be the meaningful year where people is finally released from pandemic fear and is able to go on meaningful holiday with their friends and family. With the successful Eid Holiday movie hit, Christmas is noted to be one of Indonesia’s important moment to celebrate the freedom from COVID-19 since it also happens in 2022. Online news once again becomes a media that is able to influent people and showing its dynamic in policy throughout their Christmas celebration news. Van Dijk’s analysis method is the fitting method to elaborate the policy dynamics in news media during Christmas 2022 Holiday.